2017
DOI: 10.1002/chem.201702060
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Electrophilic C−H Borylation Using NHC⋅Boranes and Iodine Forms C2‐, not C3‐, Borylated Indoles

Abstract: Activation of N‐heterocyclic carbene boranes (NHC⋅BH3) by I2 enables the metal‐free catalytic C−H borylation of heteroarenes with formation of H2 as the by‐product in a process that uses only bench stable precursors. The borylation of indoles using NHC⋅BH3/I2 produces C2‐borylated indoles exclusively in contrast to other catalytic electrophilic C−H borylation methods. Mechanistic studies indicate that this is due to C3 to C2 boron migration facilitated by the absence of exogenous Brønsted bases. Thus this C−H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 44 publications
3
30
0
Order By: Relevance
“…24 By employing the N-heterocyclic carbene-borane 7 as a boron source, Ingleson and co-workers demonstrated an I 2catalyzed C-H borylation of hetarenes, in which a C2-regioselectivity was observed in contrast to the C3-regioselectivity reported in the previous catalytic electrophilic C-H borylation (Scheme 2). 25 Mechanistic studies supported an S E Ar mechanism and indicated that the C2-regioselectivity might arise as a result of the presence of a competent Brønsted acid, the higher thermodynamic stability of C2isomers, and the ready protodeboronation of C3 isomers.…”
Section: Synpacts Syn Lettmentioning
confidence: 90%
“…24 By employing the N-heterocyclic carbene-borane 7 as a boron source, Ingleson and co-workers demonstrated an I 2catalyzed C-H borylation of hetarenes, in which a C2-regioselectivity was observed in contrast to the C3-regioselectivity reported in the previous catalytic electrophilic C-H borylation (Scheme 2). 25 Mechanistic studies supported an S E Ar mechanism and indicated that the C2-regioselectivity might arise as a result of the presence of a competent Brønsted acid, the higher thermodynamic stability of C2isomers, and the ready protodeboronation of C3 isomers.…”
Section: Synpacts Syn Lettmentioning
confidence: 90%
“…While stoichiometric C-H borylation reactions have been reported with a number of highly Lewis acidic boranes and borenium ions, 61,[149][150][151][152][153][154][155][156][157][158][159]160 these processes employ stoichiometric amounts of highly reactive reagents through a Wheland-like mechanism. In a few cases, Friedel-Crafts-type catalysis could be observed for the TM-free catalytic borylation of arenes, in mechanisms that bear little similarity to TM chemistry.…”
Section: Arene C-h Activationmentioning
confidence: 99%
“…Employing NHC-boranes and sub-stoichiometric I 2 as catalyst C 2 -borylation of indoles was achieved. 30 Substantial evidence also demonstrates a dramatic impact of I 2 as an additive on hydrogenation of Nheteroarenes. 31 Based on these studies Chang and coworkers have investigated the role of iodine as the catalyst for tandem hydrogenation of N-heteroarenes using HBpin as reducing agent.…”
Section: Hydroboration Of Heteroarenes Catalyzed By Pblock Elementsmentioning
confidence: 99%